Benchmarking of vertically integrated models for the study of the impact of caprock morphology on CO2 migration. (November 2019) - Ahmadinia, Masoud; Shariatipour, Seyed M.; Andersen, Odd; Sadri, Mahdi
Highlights: This work is the first benchmark study on the impact of caprock morphology on CO2 storage migration. A number of modelling approaches including MRST-co2lab, ECLIPSE-black-oil, ECLIPSE-compositional and ECLIPSE-VE are used. In 3D simulators, the dissolution was seen to decrease by increasing the tilt angle. Concerning the computation costs, MRST-co2lab significantly outperformed other models. Abstract: Saline aquifers constitute the most abundant geological storage option for Carbon Capture and Storage (CCS) projects. When injected in the aquifer, due to its lower density in comparison to the in-situ brine, the free phase CO2 tends to migrate upwards. This vertical migration is generally tens of metres depending on the reservoir thickness, despite the plume migration distance in the horizontal direction which could be over hundreds of kilometres (depending on the time horizon, reservoir characteristics, trapping mechanisms involved, etc.). In many situations, the plume ends up as a separate region below a sealing barrier. This large aspect ratio between the plume migration in the horizontal and vertical directions would potentially validate the use of vertical equilibrium (VE) models in CO2 storage studies. In other words, when phase segregation occurs rapidly compared to the time scale studied, vertical equilibrium can be assumed, allowing for the use of specially adapted models. In the VE model, the equilibrium between brine and CO2 is pre-assumed at all times. Under this assumption, the injected CO2 plume flow in 3D can be approximated in terms of its thickness in order to obtain a 2D simulation model, which consequently decreases the computational costs. The time by which phase segregation occurs depends on the aquifer thickness, aquifer permeability, fluid properties, etc. However, the CO2 and in-situ brine are separated considerably fast and form two separate layers, in comparison to the time period for lateral migration. The CO2lab module of the Matlab Reservoir Simulation Toolbox (MRST) used in this work, is a set of open source simulation and workflow tools to study the long-term, large-scale storage of CO2 . We employed the VE tool in MRST−CO2lab (MVE) to study the effect of caprock morphology on the CO2 migration. The results have been compared with a number of simulators including ECLIPSE-black-oil (E100), ECLIPSE-compositional (E300) and ECLIPSE-VE (EVE) models and the differences between the approaches are analysed and discussed in detail. In particular, we focused on the impact of caprock morphology and aquifer top-surface slope on the CO2 structural and dissolution trapping mechanisms and plume migration. The results indicated a good agreement for the ultimate plume shapes in all the models. However, the amount of dissolved CO2 in the brine was different.